A Analisis Mutu dan Finansial Virgin Coconut Oil (VCO) Dengan Metode Fermentasi Saccharomyces Cerevisiae - Undadraja Bigi, Bigi; Rini Hartari, Widia (Politeknik Negeri Lampung., 2023)
Coconut meat is the part that is mostly processed into coconut milk, occult oil, and copra. Downstream processing, such as VCO, is an opportunity to increase the economic value of coconut farmers. VCO contains lots of unsaturated fatty acids and antioxidants, which are good for body health. This study aims to determine the quality and antioxidant activity of VCO and its economic feasibility as a business. This research was carried out in two stages, namely the manufacture of VCO by fermentation using the addition of starter Saccharomyces cerevisiae in amounts of 1 gram, 2 grams, and 3 grams. Then the yield was calculated and tested for antioxidant activity, organoleptic color, taste, and aroma. Then the second stage is calculated financially for the VCO business. The data obtained were then analyzed descriptively. The results of the research conducted show that the production of virgin coconut oil (VCO) is enough to be used as a business; it will reach the BEP when it has sold 13 bottles or earned as much as IDR 312,918. For every rupiah spent, a sales profit of 4.79 will be obtained, with a profit per unit of production of IDR 1,187,082, so this VCO business is feasible to develop. The VCO fermentation, according to SNI 7381:2008, is the addition of 1, 2, and 3 grams of baker's yeast. But the high yield and aroma are found in the addition of 2 grams of yeast.